Mental wellness in adults with Down syndrome : a guide to emotional and behavioral strengths and challenges - McGuire, Dennis Eugene; Chicoine, Brian (Bethesda, Md. : Woodbine House, 2006)
This authoritative, easy-to-read guide clarifies what are the common behavioral characteristics of Down syndrome, how some can be mistaken for mental illness, and what are the bona fide mental health problems that occur more commonly in people with Down syndrome. As McGuire and Chicoine describe these traits and mental health issues, they also explain, through detailed observations and case studies based on their patients, how parents, caregivers and adults with Down syndrome can work together to foster mental wellness. In addition, the authors discuss the importance of regular assessment and how behavior and mental well-being can be affected by environmental conditions, social opportunities, and physical health.
Mental health assessment -- Assessing the physical/mental health connection -- Family and community support -- What is normal?: Understanding "normal," "usual," and "common," behavior in people with Down syndrome -- Memory -- Communication skills -- Self-esteem and self-image -- Self -talk, imaginary friends, and fantasy life -- The groove and flexibility -- Life span issues: "teenage behavior," isolation, withdrawal, retirement -- Mental illness and its precipitants -- Assessment of mental illness -- Treatment approaches for mental illness -- Mood disorders -- Anxiety -- Obsessive-compulsive disorder -- Psychotic disorders -- Eating refusal -- Challenging behavior -- Self-injurious behavior -- Tic disorders and repetitive movements -- Austism -- Alzheimer disease.
Includes bibliographical references (p. [415]-420) and index.
Keywords: Down syndrome